Influence of solidification process on calcined kaolin geopolymeric powder - Liew, Yun Ming; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Mohd Mustafa Al Bakri, Abdullah; Binhussain, M.; Luqman, Musa, Dr.; Khairul Nizar, Ismail, Assoc. Prof. Dr.; Che Mohd Ruzaidi, Ghazali; Cheng, Yong Heah (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/